Interfacial adhesion between embedded fibre optic sensors and epoxy matrix in composites. Issue 3 (1st February 2019) - Lima, Rosemere de A. A.; Rocca, Daniele; Da Costa, Hector R. M.; de Sousa, Juliana P. B.; Bettini, Paolo; Sala, Giuseppe; Banea, Mariana D.
Abstract: Fibre optic (FO) sensors are becoming increasingly popular for different applications in structural monitoring. Among their excellent properties, a strong interest for this type of sensors are represented by the possibility of embedding FOs inside composite components. In this case, one of the factors that significantly influence the efficiency of the whole Structural Health Monitoring (SHM) system is the interfacial adhesion between FO sensors and the host material. The main objective of this work is to investigate the interfacial adhesion between embedded fibre optic sensors and epoxy matrix to find the best type of optical fibre to be used in epoxy matrices to produce smart composites. Four types of optical fibres with different diameters and coatings (i.e. polyimide, polyacrylate and ormoceramic) were used. Pull-out tests were carried out and different methods were used to obtain the composite/optical fibre interfacial properties. Finally, an optical microscopy and Scanning Electron Microscopy (SEM) analysis were performed to characterize the fibre/matrix interfaces. It was found that the optical fibre that presented the highest energy required for interface rupture and, consequently, less invasiveness to the host material was the ormoceramic fibre with the smallest diameter.